Effect of Length of Illness on Achievement of Systolic and Diastolic Blood Pressure Therapy Targets for Grade 1 Hypertension - Suci Khasanah; Pramesti Dewi (LPPM Universitas Harapan Bangsa, 2024)
Blood pressure >140 mmHg is at high risk for cardiovascular diseases. The aim of the study was to determine the effect of length of illness on the achievement of the target of systolic blood pressure (SBP) and diastolic blood pressure (DBP) in grade 1 hypertension patients without comorbidities. The study design was cross sectional, with a sample size of 34 respondents who met the sample criteria taken from 93 grade 1 hypertension patients without comorbidities. Blood pressure data for the last 3 months based on medical records at the puskesmas and direct blood pressure measurements in the 4th month. The duration of hypertension illness was calculated from the time the doctor diagnosed it until the time of data collection, by means of interviews. Data analysis using chi square. The results of the research on the effect of length of illness on the achievement of SBP and DBP were obtained: p value 0.018, V -0.407, OR (CI) 0.134 (0.023-0.799) and p value 0.019, V -0.402, OR (CI) 0.083 (0.007-0.950). Conclusion: The more chronic you suffer from grade 1 hypertension, the lower the chances of achieving SBP and DBP therapeutic targets. Length of illness needs to be considered in the management of grade 1 hypertension patients.